2019
DOI: 10.36387/jiis.v4i1.268
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH PEMBERIAN SALEP EKSTRAK KUNYIT KUNING (Curcuma longa Linn) TERHADAP PENYEMBUHAN LUKA SAYAT PADA TIKUS PUTIH (Rattus norvegicus)

Abstract: Kunyit merupakan salah satu jenis tanaman herbal yang dipercaya dapat membantu proses penyembuhan luka. Secara ilmiah kunyit telah dibuktikan memiliki efek anti-inflamasi dan choleretik. Senyawa Kurkumin yang terdapat pada kunyit memiliki khasiat antimikroba dan antioksidan sehingga mempercepat re-epitelisasi dan migrasi sel seperti myofibroblast, fibroblast dan makrofag yang diperlukan untuk penyembuhan luka. Penelitian ini bertujuan untuk mengetahui pengaruh salep ekstrak kunyit kuning terhadap penyembuhan l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
4
0
4
Order By: Relevance
“…A gel is a semisolid system that provides a cool and soothing feeling to the skin with a high water content so it increases hydration in the stratum corneum and dries easily to form a film layer. 11 The results of this study indicate that the turmeric extract gel and Trigona honey can be used as alternative treatments for post-CS wounds. However, further research is needed on humans to determine the appropriate dose.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…A gel is a semisolid system that provides a cool and soothing feeling to the skin with a high water content so it increases hydration in the stratum corneum and dries easily to form a film layer. 11 The results of this study indicate that the turmeric extract gel and Trigona honey can be used as alternative treatments for post-CS wounds. However, further research is needed on humans to determine the appropriate dose.…”
Section: Discussionmentioning
confidence: 73%
“…10 The mechanism of action of turmeric extract on wounds is to inhibit cyclooxygenase (COX-2) and lipoxygenase, which play roles in the inflammatory stage to accelerate tissue re-epithelialization, cell proliferation, and collagen synthesis. 11 The antibacterial activity of honey is exhibited by components such as H 2 O 2 , glucose, and several polyphenols. The phenolic components inhibit bacterial growth through pro-oxidative activity by increasing H 2 O 2 activity.…”
Section: Introductionmentioning
confidence: 99%
“…Penggunaan kunyit kuning sebagai bahan penyembuhan luka mempercepat proses penyembuhan luka, karena senyawa kurkumin memiliki sifat anti-inflamasi dan antioksidan serta mendorong re-epitelisasi dan proliferasi sel dan sintesis kolagen (Milasari et al, 2019).…”
Section: Pembahasanunclassified
“…Previously (Milasari, 2019), With the title of the study the effect of giving yellow turmeric extract ointment (curcuma longa linn) on wound healing in white mice (rattus norvegicus), stated that the administration of yellow turmeric extract ointment concentrations of 10%, 20% and 30% affects the speed of wound healing in treatment rats and based on observation of anatomical pathology and post hoc tests with LSD showed that the ointment of yellow turmeric extract 10% is the best preparation in the wound healing process. Where the significant differences of each group are evident on day 7.…”
Section: Figure 1 Wound Length Reduction Graphmentioning
confidence: 99%